2015
DOI: 10.4236/as.2015.612144
|View full text |Cite
|
Sign up to set email alerts
|

Novel Investigation on Ammonium Thiosulphate (ATS) as an Inhibitor of Soil Urease and Nitrification

Abstract: Among the numerous products so far promoted as effective urease and/or nitrification inhibitors, it is possible to detect a renewed interest in environmentally friendly tools, such as ammonium thiosulphate (ATS, (NH4)2S2O3) which is currently used as fertilizer for N and S nutrition. Among contradictory results accounted in the current literature, there is reported that ammonium thiosulphate (ATS) exerts inhibitory activity at large but unlikely agronomic rates of 2500-5000 mg•kg −1 soil. We carried out a nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…(Bronson et al, 1992) 4-amino-1,2,4-6-triazole-HCl ATC Ishihada Industries (Malhi & Nyborg, 1988) 2,4-diamino-6-trichloromethyltriazine Cl-1580 American Cyanamid (Bremner & Yeomans, 1986) Dicyandiamide DCD Showa Denko y (Treweek et al, 2016) Thiourea TU Nitto Ryuso (Malhi & Nyborg, 1988) 1-mercapto-1,2,4-triazole MT Nippon No recent reference 2-amino-4-chloro-6-methylpyramidine AM Mitsui chemicals (Kumar et al, 2015) 2-sulfanilamidothiazole ST Mitsui Chemicals (Bremner & Yeomans, 1986) (Menéndez et al, 2012) 1-amide-2-thiourea ASU Nitto Chemical Ind. n (Bremner & Yeomans, 1986) Ammonium thiosulphate ATS Fertilizer (Margon et al, 2015) 3-methylpyrazole 3-MP /SKW Piesterwitz y (Barneze et al, 2015) 1H-1,2,4-triazole HPLC (Barneze et al, 2015) 5-ethylene oxide-3-trichloro- Karanjin (Datta & Adhya, 2014) Calcium carbide (Bronson et al, 1992) N (2,5 dichlorphenyl) succinic acid monoamide DCS (Skiba & Smith, 1993) Polyolefin coated urea POCU (Delgado & Mosier, 1996) 3,4 dimethylpyrazol succinic acid DMPSA Eurochem (Pacholski et al, 2016) Potassium thiosulfate KTS fertilizer (Cai, 2018) The effect of nitrification inhibitors is strongly influenced by soil and soil moisture contents. In some experiments nitrification inhibitors were completely ineffective (van der Weerden et al, 2016;Nauer et al, 2018).…”
Section: Table 15mentioning
confidence: 99%
“…(Bronson et al, 1992) 4-amino-1,2,4-6-triazole-HCl ATC Ishihada Industries (Malhi & Nyborg, 1988) 2,4-diamino-6-trichloromethyltriazine Cl-1580 American Cyanamid (Bremner & Yeomans, 1986) Dicyandiamide DCD Showa Denko y (Treweek et al, 2016) Thiourea TU Nitto Ryuso (Malhi & Nyborg, 1988) 1-mercapto-1,2,4-triazole MT Nippon No recent reference 2-amino-4-chloro-6-methylpyramidine AM Mitsui chemicals (Kumar et al, 2015) 2-sulfanilamidothiazole ST Mitsui Chemicals (Bremner & Yeomans, 1986) (Menéndez et al, 2012) 1-amide-2-thiourea ASU Nitto Chemical Ind. n (Bremner & Yeomans, 1986) Ammonium thiosulphate ATS Fertilizer (Margon et al, 2015) 3-methylpyrazole 3-MP /SKW Piesterwitz y (Barneze et al, 2015) 1H-1,2,4-triazole HPLC (Barneze et al, 2015) 5-ethylene oxide-3-trichloro- Karanjin (Datta & Adhya, 2014) Calcium carbide (Bronson et al, 1992) N (2,5 dichlorphenyl) succinic acid monoamide DCS (Skiba & Smith, 1993) Polyolefin coated urea POCU (Delgado & Mosier, 1996) 3,4 dimethylpyrazol succinic acid DMPSA Eurochem (Pacholski et al, 2016) Potassium thiosulfate KTS fertilizer (Cai, 2018) The effect of nitrification inhibitors is strongly influenced by soil and soil moisture contents. In some experiments nitrification inhibitors were completely ineffective (van der Weerden et al, 2016;Nauer et al, 2018).…”
Section: Table 15mentioning
confidence: 99%
“…Urease, which represents the class of hydrolases, plays an important role in the cycle of nitrogen (Calvarro et al, 2014;Ge et al, 2010;Hu et al, 2014;Margon et al, 2015;Nie et al, 2015). Inverse correlations were observed between the content of loosely bound metals and the activity of urease in alluvial and meadow-alluvial soils.…”
Section: Discussionmentioning
confidence: 89%
“…1 also shows that inhibiting the activities of the enzymes which catalyze the processes of nitrification and denitrification could be another approach to decrease N 2 O emissions. Previous studies showed that thiosulfate could decrease NH 4 + concentrations derived from the degradation of urea by inhibiting soil urease activity ( Margon et al., 2015 ) and reduce the N 2 O emissions from the soil applied with urea ( Cai et al., 2018 ). Dicyandiamide, hippuric acid, and benzoic acid are also well-known nitrification inhibitors that could depress soil nitrification and subsequently attenuate the N 2 O emission of urine patches from ruminants ( Bertram et al., 2009 ; Minet et al., 2018 ).…”
Section: N 2 O Formation In Cattle Excretamentioning
confidence: 99%